2015
DOI: 10.1038/onc.2014.419
|View full text |Cite
|
Sign up to set email alerts
|

Decreased miRNA-637 is an unfavorable prognosis marker and promotes glioma cell growth, migration and invasion via direct targeting Akt1

Abstract: Although increasing evidence indicated that the deregulation of microRNAs (miRNAs) contributes to tumorigenesis and invasion, little is known about the role of miR-637 in human gliomas. In the present study, we found that the expression level of miR-637 was significantly reduced in clinical glioma tissues compared with normal brain tissues. Moreover, we revealed that the introduction of miR-637 dramatically suppressed glioma cell growth, migration and invasion in vitro and in vivo. Further studies revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
112
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(117 citation statements)
references
References 36 publications
4
112
0
1
Order By: Relevance
“…Immunohistochemistry Immunohistochemistry of CCND1 (Santa Cruz Biotechnology, Santa Cruz, USA) was performed in NPC tissues according to a previous description. 6,[12][13][14][15]34 Stained tissue sections were evaluated separately by two pathologists blinded to the clinical parameters. For cytoplasmic staining, scoring was assessed based on the sum of cytoplasm staining intensity and the percentage of positive staining areas of cells.…”
Section: Collection Of Primary Npc and Non-cancerous Nasopharynx Specmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry Immunohistochemistry of CCND1 (Santa Cruz Biotechnology, Santa Cruz, USA) was performed in NPC tissues according to a previous description. 6,[12][13][14][15]34 Stained tissue sections were evaluated separately by two pathologists blinded to the clinical parameters. For cytoplasmic staining, scoring was assessed based on the sum of cytoplasm staining intensity and the percentage of positive staining areas of cells.…”
Section: Collection Of Primary Npc and Non-cancerous Nasopharynx Specmentioning
confidence: 99%
“…[1][2][3][4][5][6] Hence, understanding the expression profile and function of individual miRNAs will help to validate their use as diagnostic markers and also provide therapeutic targets for cancer treatment. miR-374a was first reported to be upregulated in primary small cell lung cancer compared to normal lung tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The target mRNA molecules are then silenced by one or more of the following processes: cleavage of the mRNA strand into two pieces, destabilization of the mRNA through shortening of its polyA tail, and preventing translation of mRNA into protein [9,10]. As important regulatory molecules, miRNAs are involved in multiple cellular processes, including development [11][12][13], proliferation [14][15][16][17], migration [16,[18][19][20], and apoptosis [17,21,22]. Studies have demonstrated that miRNAs are linked with various cancers and tumors in humans [23][24][25][26].…”
Section: Introductionmentioning
confidence: 98%
“…Despite advances in cancer treatment, this statistic has not changed significantly (2,3). Previous reports have suggested that several genes contribute to the pathogenesis of glioma, including protein-coding genes (4,5), microRNAs (miRNAs) (6) and long non-coding RNAs (lncRNAs) (7,8). However, the mechanisms of the majority of genes in glioma remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The U251 cells were incubated in 6-well plates for 24 h at a density of 2ⅹ10 6 cells/well and then were transfected using DMEM and polybrene reagents (Santa Cruz Biotechnology, Inc., Dallas, TX, USA) according to the manufacturer's protocol at a multiplicity of infection of 1. The U251 human glioma cells were maintained in Dubecco's modified Eagle's medium (DMEM) with high glucose and sodium pyruvate, supplemented with 10% FBS and antibiotics (100 U/ml penicillin and 100 mg/ml streptomycin), and plus 2 µg/ml puromycin for 2 weeks to gain stable clones.…”
Section: Lentiviral Construction and Cell Transfectionmentioning
confidence: 99%